A neutron dark-field imaging study towards guiding magnetic flux in electric steel sheets through laser shock peening - Jiazhou Shen; Matteo Busi; Peter Rauscher; Jacopo Valsecchi; Gergely Nemeth; Markus Strobl (Scientific Reports)
Abstract Well-designed guidance of the magnetic field through electric steel sheets forming the rotor of electrical motors and generators is of utmost importance with regards to efficiency. Typically, this is achieved through tailored cutouts in the sheets. While fulfilling the magnetic guidance needs this strategy structurally weakens the rotor and ultimately limits the possible rotation speeds due to the mechanical forces these imply. Recently an alternative approach has been reported, in which the material is embossed in respective regions. The, thus, induced stresses act, based on the inverse magnetostrictive effect, as flux barriers without, unlike traditional cutouts, weakening the structure significantly. Here we propose to replace the embossing through laser shock peening, which can be controlled digitally and hence be applied flexibly, without the need for mechanical changes in the production lines, like in the case of a punch.